Etude de la faisabilité technique et économique de l’installation d’un échangeur de chaleu - Abdessamia, Hadjadj (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2021)
Abstract : In the present work of this thesis, experimentally and modeling investigations of the effect of mass flow rate on the performance of a Helicoidal Water Air Heat Exchanger (HWAHE) in the region of El-Oued (south-east of Algeria), were undergone. On the basis of the obtained results, an experimental study of the refreshing strategy (HWAHE) system in the El Oued region, it was shown that a great potential of the earth to air heat exchanger technique for buildings and agricultural greenhouses in arid regions preheating or precooling may be ensured. The HWAHE made of PVC piping with 30 m of length and 0.06 m of diameter was immersed into the bottom of a water well at 5 m depth. In addition, a theoretical model was developed to determine the evolution of the air temperature inside the HWAHE as function of the main operating parameters. It is found that the exchanger is mainly depending on the mass flow rate. As results, the maximum heat exchange reached nearly 418 W at 0.035 kg. s−1 of mass flow rate while the maximum of temperature gap between the inlet and the outlet air was 14.1 o C. The HWAHE efficiency decreased with the increase of the mass flow rate. The efficiency of heat exchanger was obtained to be 82%, 81% and 80% for the average velocity value of 0.035, 0.05 and 0.07 kg. s−1, respectively. In addition, exergitical and economical investigate were carried out. The HWAHE energy and exergy efficiencies are maximal, and they reach to 92% and 89%, respectively. الملخص: في العمل الحالي لهذه الرسالة ، أجريت دراسات تجريبية ونمذجة لتأثير التدفق الكتلي للهواء على أداء مبادل حراري حلزوني أرضي (Helicoidal water-air heat exchanger :HWAHE) في منطقة الواد (جنوب شرق الجزائر) . على أساس النتائج متحصل عليها ، دراسة تجريبية لاستراتيجية التجديد لنظام المبادل الحراري HWAHE) (في منطقة الوادي ، تبين أن هناك إمكانات كبيرة لتقنية هذا المبادل في التبريد والتسخين للمباني والزراعة. قد يتم ضمان التسخين المسبق أو التبريد المسبق في البيوت الزراعية في المناطق القاحلة. حيث يتم غمر HWAHE المصنوع من أنابيب PVC بطول 30 مترًا وقطرها 0.06 مترًا في قاع بئر ماء على عمق 5 أمتارللتأدية الغرض. بالإضافة إلى ذلك ، تم تطوير نموذج نظري لتحديد تطور درجة حرارة الهواء داخل HWAHE كدالة لمعلمات التشغيل الرئيسية. وجد أن المبادل يعتمد بشكل أساسي على معدل التدفق الشامل. ونتيجة لذلك ، بلغ الحد الأقصى للتبادل الحراري ما يقرب من 418 وات عند تدفق 0.035 كغ / ث من الهواء بينما كانت أقصى فجوة في درجة الحرارة بين مدخل ومخرج المبادل 14.1 درجة مئوية. انخفضت كفاءة HWAHE مع زيادة معدل التدفق الشامل. بلغت كفاءة المبادل الحراري 82٪ و 81٪ و 80٪ لمتوسط قيمة السرعة 0.035 و 0.05 و 0.07 كغ / ثانية على التوالي. بالإضافة إلى ذلك ، تم إجراء دراسة جدوى او تحقيق اقتصادي وتحليل طاقوي. حيث تعد كفاءات طاقة HWAHE وكفاءة الطاقة القصوى ، وتصل إلى 92٪ و 89٪ على التوالي.
géothermique dans la région d’El Oued-Algérie-
Thése de l’obtention du diplôme Doctorat Option Energétique
Keywords: Geothermal energy; Helicoidal Water Air Heat Exchanger; Energy and Exergetic analysis; Thermal performance; Energy saving.; مبادل حراري, التبريد والتسخين, كفاءة المبادل الحراري, تحقيق اقتصادي ، تحليل طاقوي , كفاءة الطاقة.